Interactive Liveworksheet-based learning on chemical reaction rates to enhance high school students’ learning outcomes - Firnanda, Ferdila Ayu; Sukarmin, Sukarmin (Universitas Islam Negeri Raden Intan Lampung, 2026)
The reaction rate is often an obstacle for high school students because of its abstract nature and because it is not directly observable. This research develops Liveworksheet-based electronic student worksheets (e-worksheets) by integrating submicroscopic animations, contextual videos, and interactive questions into a single platform. This approach has not been widely applied to chemistry learning in Indonesia. The 4D model was chosen for its systematic, validated structure for developing learning tools and was applied alongside the Think-Pair-Share (TPS) model to encourage active student collaboration. A total of 34 grade XI students at SMAN 10 Surabaya were involved in the design of a one-group pretest-posttest trial. Three expert validators conducted validation; practicality was assessed through questionnaires and observations; and effectiveness was analyzed using N-Gain and the Wilcoxon Test. The validation results showed a mode score of 4–5, an average N-Gain of 0.81 (high category), and a practicality of 89.20% (excellent). The Wilcoxon test confirmed a significant improvement in learning outcomes (Z = −5.105; p < 0.05). This e-worksheet has the potential to be adapted as an inclusive digital learning medium for other chemistry topics and for broader educational levels.